First-line mFOLFOX plus cetuximab followed by mFOLFOX plus cetuximab or single-agent cetuximab as maintenance therapy in patients with metastatic colorectal cancer: Phase II randomised MACRO2 TTD study. (September 2018) - Aranda, E.; García-Alfonso, P.; Benavides, M.; Sánchez Ruiz, A.; Guillén-Ponce, C.; Safont, M.J.; Alcaide, J.; Gómez, A.; López, R.; Manzano, J.L.; Méndez Ureña, M.; Sastre, J.; et al.
Abstract: Background: This multicentre, randomised, and phase II study evaluated mFOLFOX+cetuximab followed by maintenance mFOLFOX+cetuximab or single-agent cetuximab in metastatic colorectal cancer (mCRC) patients (NCT01161316). Patients and methods: Previously, untreated mCRC patients (wild-type  KRAS ) were randomised to receive cetuximab+mFOLFOX-6 (8 cycles for 2 weeks) followed by maintenance therapy: single-agent cetuximab (Arm-A) or mFOLFOX-6 + cetuximab (Arm-B) until progression. Primary endpoint was progression-free survival (PFS) at 9 months. Results: One hundred ninety-three patients (median [range] age 60 [33–74] years) were randomised (2:1): 129 Arm-A versus 64 Arm-B. PFS at 9 months (95% confidence interval) showed non-inferiority between arms (Arm-A/Arm-B: 60 [52, 69]%/72 [61, 83]%, p [non-inferiority]<0.1). There were no statistically significant differences in the PFS (Arm-A/Arm-B: 9 [95% CI 7, 10] months/10 [7, 13] months, hazard ratio [HR] = 1.19 [0.80, 1.79]) or overall survival (23 [19, 28] months/27 [18, 36] months, HR = 1.24 [0.85, 1.79]) between arms. The objective response rate was also similar (48 [39, 57]%/39 [27, 52]%). The safety profile was similar between arms, and all patients experienced at least one adverse event (AE) (Arm-A/Arm-B grade ≥III AEs: 70%/68%). The most common grade ≥III AEs were as follows: neutropenia (Arm-A/Arm-B: 28%/26%), rash acneiform (15%/24%) and sensory neuropathy (2%/15%) in any group. Arm-A was associated with less grade ≥III rash and sensory neuropathy and a lower rate of serious AEs (20%/27%). Conclusion(s): This phase II exploratory trial with a non-inferiority design suggests that maintenance therapy with single-agent cetuximab following mFOLFOX+cetuximab induction could be a valuable option compared with mFOLFOX+cetuximab treatment continuation. We await phase III trials to confirm single-agent cetuximab as maintenance therapy in mCRC patients. Highlights: Cetuximab alone could be a viable maintenance therapy option in metastatic colorectal cancer patients. Progression-free survival (PFS) at 9 months was similar between cetuximab alone and FOLFOX+cetuximab. PFS and overall survival were similar between cetuximab alone and FOLFOX+cetuximab. Safety profile was similar between cetuximab alone and FOLFOX+cetuximab.